Monitoring and Dose Assessment for Children Following a Radiation Emergency—Part II: Calibration Factors for Thyroid Monitoring. Issue 3 (September 2019) - Li, Chunsheng; Tremblay, Marilyn; Capello, Kevin; Kurihara, Osamu; Youngman, Mike; Etherington, George; Ansari, Armin; López, María Antonia; Franck, Didier; Dewji, Shaheen
Abstract : Abstract: Past radiological and nuclear accidents have demonstrated that monitoring a large number of children following a radiological and nuclear emergency can be challenging, in accommodating their needs as well as adapting monitoring protocols and applying age-specific biokinetics to account for various ages and body sizes. This paper presents the derived calibration factors for thyroid monitoring of children of all ages recommended by the International Commission on Radiological Protection using four selected detectors at given times following a short-term (acute) intake of 131 I by inhalation. These calibration factors were derived by Monte Carlo simulations using the models of various detectors and pediatric voxel phantoms. A collection of lookup tables is presented in this paper which may be directly used as a quick reference by emergency response personnel or technical experts performing thyroid monitoring and assessment without doing time-consuming calculations.